Effects of Different Hosts on Bacterial Communities of Parasitic Wasp Nasonia vitripennis - Duan, Ruxin; Xu, Heng; Gao, Shanshan; Gao, Zheng; Wang, Ningxin (Frontiers in Microbiology, 2020)
Parasitism is a special interspecific relationship in insects. Unlike most other ectoparasites, Nasonia vitripennis spend most of its life cycle (egg, larvae, pupae and early adult stage) inside the fly pupae, which is covered with hard puparium. Microbes play important roles in host development and help insect hosts to adapt to various environments. How the microbes of parasitic wasp respond to different fly hosts living in such close relationships motivated this investigation. In this study, we used N. vitripennis and three different fly pupa hosts (Lucilia sericata, Sarcophaga marshalli, and Musca domestica) to address this question, as well as to illustrate the potential transfer of bacteria through the trophic food chains. We found that N. vitripennis from different fly pupa showed distinct microbiota, which means that the different fly hosts could affect the bacterial communities of their parasitic wasps. Some bacteria showed potential horizontal transfer through the trophic food chains, from the food through the fly pupae to the parasitic wasp. We also found that the heritable endosymbiont Wolbachia could transferred from the fly host to the parasite and correlated with the bacterial communities of the corresponding parasitic wasps. Our findings provide new insight to the microbial interactions between parasite and host.